Puasa sebagai Disiplin Spiritual: Studi Komparatif antara Ramadan dalam Islam dan Lent dalam Kristen - Haryani Haryani; Garcia Kristin Rompas; Kristin Parera Lengkey (Kamali: Jurnal Ilmu Agama, 2025)
Fasting remains a vital religious practice in today’s fast-paced modern culture, yet comparative studies specifically examining the mechanisms by which fasting fosters spiritual discipline across traditions are limited. This study aims to operationally identify the theological and ritual differences between Ramadan in Islam and Lent in Christianity, analyze the mechanisms by which fasting fosters spiritual discipline, and evaluate its practical implications for moral resilience and social responsibility. Using qualitative methods grounded in the literature, this study employs hermeneutic analysis of normative texts and thematic analysis of theological literature, progressing through the stages of source selection, contextual reading, and comparative synthesis. Triangulation is employed to ensure validity. The results reveal three main mechanisms that consistently emerge across both traditions: first, time-bound and repetitive ritual structures that strengthen impulse control and the stability of self-discipline; second, communal practices, such as Ramadan ifṭar and Lenten charity services, that foster empathy, solidarity, and a sense of social responsibility; and third, the practice of spiritual reflection through prayer, repentance, and muhasabah, which deepens moral awareness and strengthens ethical orientation. The analysis also revealed differences in theological emphasis: Ramadan emphasises the vertical relationship between the individual and God, as well as collective charity. In contrast, Lent emphasises self-denial and personal transformation. These findings indicate the potential of fasting as a medium for developing spiritual disciplines across traditions and a basis for more constructive interfaith dialogue.